EFEKTIFITAS MODEL KARAKTERISTIK ARUS LALU LINTAS PADA RUAS JALAN SIMPANG 4 BIREUN (PERBANDINGAN DENGAN METODE GREENSHIELD, GREENBERG, UNDERWOOD) - Adzuha - Desmi; Lis Ayu Widari; Riza Yanti (Teras Jurnal : Jurnal Teknik Sipil, 2019)
AbstractCharacteristics of the traffic flow are studied and analyzed using several methods. This study aims to analyze the comparison of traffic characteristic model on Simpang 4 Bireun road using MKJI 1997 method, and to compare with Greenshield, Greenberg and Underwood models. The effectiveness and efficiency of  the data presentation presented by each method. The results of the mathematical model for Greenshield Model are (S) = 40.6231 km/hr, Greenberg (S) = 37.92 km/hr and Underwood (S) = 40.668 km/hr. For the relationship of density velocity, Greenberg has a better approach, whereas for the density volume relationship, they show almost the same result, and for the volume velocity relationship, the Greenshield and Underwood approaches are still better. Keywords :   Greenshield, Greenberg, Underwood, Speed Vehicles, Traffic Flow,  Density of Traffic.